2011
DOI: 10.1017/s1743921312014913
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Novae: What Do We Know about Them?

Abstract: Abstract. Recurrent novae (RNe) belong to the group of cataclysmic variables that exhibit nova outbursts at intervals on the order of decades. They are rare, with 10 Galactic RNe known to date. Two are known in the LMC, while there are a few suspected RNe in M31. Nova outburst models require a high accretion rate on a massive white dwarf to explain the recurring nova outbursts, making this class of objects one of the most likely progenitor binary systems of Type Ia supernovae. The observational properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Depending on the main source of the energy the symbiotics can be divided into two groups: (a) Symbiotics with steady nuclear burning, in which the mass accretion rate is high enough to maintain (fuel) steady nuclear burning; and (b) Accretion powered symbiotics, in which the mass accretion rate is below the limit of steady nuclear burning and the energy source is the accretion. The accretion-powered symbiotics can display recurrent nova outbursts-the best examples probably are RS Oph and T CrB (Anupama 2013) and collimated jets-for example, CH Cyg, MWC 560, and PN Sa 3-22 (Leedjarv 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the main source of the energy the symbiotics can be divided into two groups: (a) Symbiotics with steady nuclear burning, in which the mass accretion rate is high enough to maintain (fuel) steady nuclear burning; and (b) Accretion powered symbiotics, in which the mass accretion rate is below the limit of steady nuclear burning and the energy source is the accretion. The accretion-powered symbiotics can display recurrent nova outbursts-the best examples probably are RS Oph and T CrB (Anupama 2013) and collimated jets-for example, CH Cyg, MWC 560, and PN Sa 3-22 (Leedjarv 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Classical novae (CNe) outbursts occur in AWB systems on the surface of the WD as a result of an explosive burning of accreted material (Thermonuclear Runaway-TNR) causing the ejection of 10 −7 to 10 −3 M ⊙ of material at velocities up to several thousand kilometers per second (Shara, 1989;Livio, 1994;Starrfield, 2001;Bode and Evans, 2008). The classical nova systems have an initial low level accretion phase (≤10 −10 M ⊙ yr −1 ; see Hillman et al in this Special Issue), where the recurrent nova (RN) that is found in outburst with 20-100 years of occurance time, generally show higher accretion rates at the level of 10 −8 -10 −7 M ⊙ yr −1 (Anupama, 2013). Once the critical pressure at the base of the WD envelope is reached (e.g., 10 19 dyn cm −2 ) the temperatures reach T∼10 8 K under semi-degenerate conditions, and a TNR occurs, resulting in the explosive burning of the hydrogen on the surface of the WD.…”
Section: X-ray Observations Of Classical and Recurrent Novaementioning
confidence: 97%
“…The next two columns shows the binary orbital period and mass of the white dwarf and the last two columns give the brightness in V band measured during the outburst peak and quiescence. References: (Schaefer 2010;Anupama 2013).…”
Section: Introductionmentioning
confidence: 99%